Answer:
see below
Step-by-step explanation:
(ab)^n=a^n * b^n
We need to show that it is true for n=1
assuming that it is true for n = k;
(ab)^n=a^n * b^n
( ab) ^1 = a^1 * b^1
ab = a * b
ab = ab
Then we need to show that it is true for n = ( k+1)
or (ab)^(k+1)=a^( k+1) * b^( k+1)
Starting with
(ab)^k=a^k * b^k given
Multiply each side by ab
ab * (ab)^k= ab *a^k * b^k
( ab) ^ ( k+1) = a^ ( k+1) b^ (k+1)
Therefore, the rule is true for every natural number n
Answer:
p yellow 11 over 15
Step-by-step explanation:
I hope you get it right! Please give me brainliest!
It could be 2+1 beacuse it says there are twice as many
Answer:
ok so 3-1.7=1.3
Step-by-step explanation:
this is bc 3-1=2-0.7=1.3
Answer:
Here look at this graph this is your answer.